Frosty the Snowman ; Frosty's winter wonderland [videorecording (DVD)] - Muller, Romeo; Durante, Jimmy, 1893-1980 (Universal, 2023)
Frosty the Snowman : "Discover how everyone's favorite happy, jolly soul came to life one day in the original holiday special, Frosty the Snowman! After Karen and her friends build a snowman on Christmas Eve, Frosty comes alive with a little help from a discarded magic hat. As temperatures rise, Karen must help Frosty get to the North Pole before he melts. At the same time, they are also being chased by Professor Hinkle who wants his magic hat back" --